A new insightful exploration into a low profile ultra-wide-band (UWB) microstrip antenna for DS-UWB applications. Issue 15 (13th October 2021) - Sarkar, Tanmoy; Ghosh, Abhijyoti; Chakraborty, Subhradeep; Singh, L. L. K.; Chattopadhyay, Sudipta
Abstract : Designing a simple and planar antenna for high speed short distance ultra-wideband (UWB) communication has become a buzzword over the last few years. There are two very different categories of UWB technologies of vital relevance, i.e. (i) carrier-free direct sequence UWB (DS-UWB), and (ii) the Multi-Band orthogonal frequency division multiplexing UWB (OFDM UWB) technology. In, Multi-Band OFDM UWB technology, multi narrowband UWB antennas with frequency notches are required. However, in DS-UWB technology, the frequency spectrum of very short duration transmitted pulses occupies wide bandwidth, and hence to transmit it, the antenna should be fully matched over the entire bandwidth without the presence of any frequency notch. In this paper, a novel, small and completely planar air gap and defected ground slot integrated rectangular microstrip antenna with dual shorting posts have been thoroughly investigated to yield UWB, i.e. (109%) bandwidth without the presence of any frequency notch.